Subjective and objective evaluation of fabric handle characteristics - Abu Bakar , Bachik (2004)
This dissertation presents the discussion amongst previous researchers to clearly define fabric hand accurately. In general, the assessment of fabric hand can be accomplished by subjective and objective methods. Subjective assessment treats fabric hand as a psychological reaction obtained from the sense of touch. On the other hand, objective assessment attempts to find the relationships between fabric hand and some physical or mechanical properties of a fabric measured objectively. Equipment and test methods to measure mechanical properties which are evolved over a number of years before the development of the KES-F system are highlighted. The principle measurements of the KES-FB and the FAST system are clearly explained, as well as the use of the interpreted data. An alternative approach which is more simple, inexpensive and reliable for objective hand evaluation has been suggested to replace all the previous equipment. Lastly, the applications of fabric objective measurement in the field of the textile and clothing industries were highlighted.